Reproduction of saguiru Steindachnerina elegans (Steindachner, 1874) (Pisces: Curimatidae) in the São Francisco River, downstream from a large reservoir in south-eastern Brazil - CAMPOS FILHO,LÍVIO GIORGIO L. DE (2022)
Abstract The gametogenesis and reproduction of S. elegans from the São Francisco River at Três Marias, Minas Gerais, were analyzed in this study. Steindachrina elegans is a species abundant in the São Francisco River basin and an important fish in the food chain. The size at first gonadal maturation (indicated by the total length of the shortest spermatid male and spawned female) was 10.5 cm and 15.0 cm, respectively. Reproduction occurred more frequently from September to April. This period had high water temperature values. A high frequency of females was observed at the mature and spawned stages and height gonadosomatic index (GSI). Meanwhile, in males, the reproductive peak was from November to February. The long spawning period and the histological characteristics of the spawned ovaries that contained oocytes at different stages of development along with post-ovulatory and atretic oocytes indicates that the spawning of S. elegans is of the partial type.